“Policy Change”. Which Are Its Dimensions and How Can It Be Measured? - Viñas, Verónica; Page, Angie; Pike, Elizabeth (Revista del CLAD Reforma y Democracia, 2018)
The theoretical debate on policy change has been consolidated since the early 90s. However, the different approaches on the subject have evolved separately, there was no communication between them. This has limited the progress in the policy change definition, making it difficult to analyse it empirically and measure it. Therefore, to address the analysis of the process of change of one specific policy, it is important to consider first: What is “policy change” according to the main theoretical approaches on this subject? Is it possible to distinguish different dimensions to operationalize the empirical analysis of the processes of change in policy? What is appropriate to measure in each dimension of change? What questions and indicators are advisable for the analysis of each dimension? Can the same questions and indicators be used to measure the change processes of different policies, to allow comparisons and feedback between empirical researches? In order to answer these questions, a research that review of the main theoretical approaches on policy change was carried out, concluding that “policy change” is a complex concept. While there are much research focused on policy change, not all of them explain in detail what this concept means from their perspective. Therefore, it is interesting to focus on the dimensions of policy change and reflect how to measure them. The research also concludes that the process of policy change can include the following dimensions: changes in the discourses and theories in use, changes in attitudes, changes in procedures, changes in the policy content, changes in behaviour and changes in the policies recipients. Each one of these dimensions can be analysed through different questions and indicators. This article presents a summary of this part of the research with examples based on the analysis of a specific policy, making concrete and operative proposals for empirical research. These reflections and proposals on how to measure policy change can be useful for research focused on change in any area of public action.